INVESTMENTS AS A KEY FACTOR OF REGIONAL FOREIGN ECONOMIC ACTIVITY: THE CASE OF KASHKADARYA REGION - Valiev Oybek; Ergashov Ziyodullo (Bright Mind Publishing, 2025)
This study examines the impact of investment on the development of foreign economic activity in the Kashkadarya region of Uzbekistan. Since the implementation of national economic reforms in 2016, the region has received increasing support to attract both domestic and foreign investment. The research focuses on how investment in sectors such as energy, agriculture, and manufacturing has contributed to export growth, industrial development, and regional integration into international markets. Using trade data, investment project reports, and policy documents, the study highlights positive outcomes as well as existing challenges, including limited infrastructure and regulatory barriers. The findings suggest that well-targeted investment policies and institutional support are essential for enhancing the region’s foreign trade capacity and ensuring long-term economic progress.